The Role of Educational Program Evaluation in Optimizing the Quality of Learning at MA Nurul Fadhilah - Erliani, Salsabila; Azzahra, Aliyyah Putri; Nasution, Inom; Rahayu, Putri; Maulana, Muhammad Rizki; Fathurrahman, Ok Reza; Tanjung, Wardah Kholilah; Amanda, Syahfira (ALACRITY : Journal of Education, 2024)
Evaluation of educational programs is an effort to find out the goals of education, it can also be interpreted as an effort to provide information that will later be conveyed to decision makers. This study is intended to review how evaluation of educational programs can play a role in optimizing the quality of learning. By using a qualitative ethnographic research approach in which we conducted direct observations and interviews with one of the teaching staff at the target school, this study found: First, evaluation activities were carried out regularly on a weekly basis. Second, the method used in evaluating madrasas is through standards of infrastructure, curriculum and financing. Third, the educational program implemented is a question and answer pattern regarding children's talents and interests. This makes it easier for educational staff to find out which programs are suitable to be implemented. Thus, evaluation of educational programs plays a very important role in improving the quality of learning.